The Description Of The Level Of Knowledge About Traditional Turmeric-Tamarind Herbal Drink As A Swamedication Of Dymenorore In Adolescent Women In Batang District Indonesia - Hasna Nuansa Sasadara; Annisa Krisridwany; Vella Lailli Damarwati; Salmah Orbayinah (LPPM - Universitas Muhammadiyah Banjarmasin, 2023)
Self-medication is an individual's effort to treat a disease that is experienced without medical assistance. Adolescent girls with a history of dysmenorrhea often do pharmacological therapy such as the use of pain relievers with a limited level of knowledge, while there are alternatives to self-medication, namely non-pharmacological therapies such as the use of herbal medicine, turmeric tamarind herbal drink, which is easily obtained and also has many benefits in treating dysmenorrhea to describe the level of knowledge about the herbal medicine turmeric tamarind as a self-medication for dysmenorrhea among adolescents in Batang District Indonesia using a non-experimental observational research design with a cross-sectional approach conducted in Batang District, Central Java in October 2021-February 2022. The population in this study, which are adolescent girls in Batang District who are currently studying for Junior High School, Senior High School with total of 5,705 respondents. The number of samples were 105 respondents. The data analysis used is the presentation technique. Based on the characteristic of respondents, most of the respondents (54.3%) belonged to the category of middle adolescents (13-15 years), and most of the respondents' education level were currently pursuing high school education (65.7%). The level of knowledge shows that most respondents have a high level of knowledge (95.2%), 2.9% respondents have a moderate level of knowledge, and 1.9% respondents have a low level of knowledge. Respondents in Batang District have a high level of knowledge or understand